Utilisation Trend of Long-Acting Insulin Analogues including Biosimilars across Europe: Findings and Implications - Godman, Brian; Wladysiuk, Magdalene; McTaggart, Stuart; Kurdi, Amanj; Allocati, Eleonora; Jakovljevic, Mihajlo; Kalemeera, Francis; Hoxha, Iris; Nachtnebel, Anna; Sauermann, Robert; Hinteregger, Manfred; Marković-Peković, Vanda; et al. (BioMed research international, 2021)
BACKGROUND: Diabetes mellitus rates and associated costs continue to rise across Europe enhancing health authority focus on its management. The risk of complications is enhanced by poor glycaemic control, with long-acting insulin analogues developed to reduce hypoglycaemia and improve patient convenience. There are concerns though with their considerably higher costs, but moderated by reductions in complications and associated costs. Biosimilars can help further reduce costs. However, to date, price reductions for biosimilar insulin glargine appear limited. In addition, the originator company has switched promotional efforts to more concentrated patented formulations to reduce the impact of biosimilars. There are also concerns with different devices between the manufacturers. As a result, there is a need to assess current utilisation rates for insulins, especially long-acting insulin analogues and biosimilars, and the rationale for patterns seen, among multiple European countries to provide future direction. Methodology. Health authority databases are examined to assess utilisation and expenditure patterns for insulins, including biosimilar insulin glargine. Explanations for patterns seen were provided by senior-level personnel. RESULTS: Typically increasing use of long-acting insulin analogues across Europe including both Western and Central and Eastern European countries reflects perceived patient benefits despite higher prices. However, activities by the originator company to switch patients to more concentrated insulin glargine coupled with lowering prices towards biosimilars have limited biosimilar uptake, with biosimilars not currently launched in a minority of European countries. A number of activities were identified to address this. Enhancing the attractiveness of the biosimilar insulin market is essential to encourage other biosimilar manufacturers to enter the market as more long-acting insulin analogues lose their patents to benefit all key stakeholder groups. CONCLUSIONS: There are concerns with the availability and use of insulin glargine biosimilars among European countries despite lower costs. This can be addressed.
Keywords: biosimilární léčivé přípravky; Diabetes Mellitus; Hypoglycemic Agents; hypoglykemika; dlouhodobě působící inzulin; vzdělávání pacientů jako téma; inzulin glargin; Humans; Insulin, Long-Acting; Patient Education as Topic; Insulin Glargine; lidé; diabetes mellitus; analýza nákladů a výnosů; Cost-Benefit Analysis; Biosimilar Pharmaceuticals; Evropa; Europe